Environmental Life-Cycle Analysis of Hybrid Solar Photovoltaic/Thermal Systems for Use in Hong Kong - Tin-Tai Chow; Jie Ji (International Journal of Photoenergy)
While sheet-and-tube absorber is generally recommended for flat-plate photovoltaic/thermal (PV/T) collector design because of the simplicity and promising performance, the use of rectangular-channel absorber is also tested to be a good alternative. Before a new energy technology, like PV/T, is fully implemented, its environmental superiority over the competing options should be assessed, for instance, by evaluating its consumption levels throughout its production and service life. Although there have been a plenty of environmental life-cycle assessments on the domestic solar hot water systems and PV systems, the related works on hybrid solar PV/T systems have been very few. So far there is no reported work on the assessment of PV/T collector with channel-type absorber design. This paper reports an evaluation of the energy payback time and the greenhouse gas payback time of free-standing and building-integrated PV/T systems in Hong Kong. This is based on two case studies of PV/T collectors with modular channel-type aluminium absorbers. The results confirm the long-term environmental benefits of PV/T applications.